The Pilbara Mesoarchean conglomerate gold versus Quaternary colluvial gold: are they genetically linked?. Issue 1 (1st December 2019) - Spinks, Sam; Pearce, Mark; Le Vaillant, Margaux; Fox, David
Summary: Recently discovered nugget gold (Au) in boulder conglomerate between the Mesoarchean West Pilbara Superterrane basement and the overlying volcano-sedimentary stratigraphy of the Neoarchean Fortescue Group in Western Australia have drawn comparisons with the famous Witwatersrand conglomerate Au deposits. Links have also been made between the Pilbara conglomerate gold and nugget Au occurrences in Quaternary colluvial deposits throughout the region. However, little is known about the origin of these as they are hitherto critically unstudied. Therefore, any genetic link is uncertain. Understanding the source and deposition of these nugget Au deposits is critical to aid further exploration in the region. Here we present a detailed study on the texture, composition and sedimentology of the nugget Au and their host rocks. The Archean conglomerate Au is comprised of a central nugget that is overgrown by a barren chloritic halo, which is further enveloped by a wider halo of Au-bearing chlorite. The central nuggets show no evidence for sedimentary transport, and have faceted surface textures consistent with chlorite imprinting. We argue these represent a modified placer deposit, with surface evidence for sedimentation removed by partial dissolution post-deposition. The Quaternary colluvial nugget Au is hypogene in origin, with minor flattening and limited silver (Ag) leaching on their surface indicative of limited colluvial-fluvial transport from source. Furthermore, preserved facets on their surface are similar to those in the Archean conglomerate deposits. We propose the source of the Quaternary colluvial nugget Au was a modified placer deposit within a proximal Archean colluvial-conglomerate that has been eroded in situ.